2018
DOI: 10.1002/glia.23513
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of oligodendrocyte gap junctions in inflammatory demyelination

Abstract: Gap junctions (GJs) coupling oligodendrocytes to astrocytes and to other oligodendrocytes are formed mainly by connexin47 (Cx47) and a smaller portion by connexin32 (Cx32). Mutations in both connexins cause inherited demyelinating disorders, but their expression is also disrupted in multiple sclerosis (MS). To clarify whether the loss of either Cx47 or Cx32 could modify the outcome of inflammation and myelin loss, we induced experimental autoimmune encephalomyelitis (EAE) in fully backcrossed Cx32 knockout (KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…This reduction is also observed in active and chronic lesions in MS, neuromyelitis optica (NMO) and Baló's disease [80]. Absence of Cx47 or Cx32 in oligodendrocytes exacerbates clinical EAE in mice associated with increased myelin loss but does not affect Cx30 and Cx43 expression in astrocytes [81]. Pathogenic mutations in Cx32 also contribute to Charcot-Marie-Tooth disease characterized by peripheral demyelination and neuropathy [80].…”
Section: Gap Junctions Connect Astrocytes and Oligodendrocytesmentioning
confidence: 99%
“…This reduction is also observed in active and chronic lesions in MS, neuromyelitis optica (NMO) and Baló's disease [80]. Absence of Cx47 or Cx32 in oligodendrocytes exacerbates clinical EAE in mice associated with increased myelin loss but does not affect Cx30 and Cx43 expression in astrocytes [81]. Pathogenic mutations in Cx32 also contribute to Charcot-Marie-Tooth disease characterized by peripheral demyelination and neuropathy [80].…”
Section: Gap Junctions Connect Astrocytes and Oligodendrocytesmentioning
confidence: 99%
“…Several studies have also provided the role of oligodendrocyte connexins in acquired demyelinating CNS disorders, in particularMS and related experimental models [80,81]. They also appear to have a regulatory role in neuroinflammation as their absence further aggravates inflammatory demyelination [82].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Cx47 KO mice developed EAE more rapidly while the EAE phenotype was more severe in Cx47 KO mice compared with Cx32 KO mice and in turn, both connexin mutants showed more severe manifestations compared with WT mice. Moreover, pathological analysis revealed that Cx47 KO mice developed more myelin and axonal loss than did WT and Cx32KO mice [27]. Extensive microglia/ macrophage activation with increased Iba-1 immunoreactivity was observed in all EAE groups, but this inflammatory activity was significantly greater in Cx47 KO EAE mice (Figure 1).…”
Section: Oligodendrocyte Connexin Pathology In Experimental Autoimmunmentioning
confidence: 95%
“…Motivated by the genetic disorders of oligodendrocyte connexins, and prominent inflammatory changes resulting from them, recent studies have also provided insight into their role in acquired demyelinating CNS disorders, in particular, multiple sclerosis (MS) and related experimental models [23][24][25][26]. These studies revealed that oligodendrocyte connexins are not only disrupted in MS lesions and beyond, but they also appear to have a regulatory role in neuroinflammation as their absence further exacerbates inflammatory demyelination [27]. In this review, we highlight the important role of oligodendrocyte connexins, in particular, Cx32 and Cx47 in the normal function of CNS, by introducing insights from genetic and experimental demyelination models.…”
Section: Introductionmentioning
confidence: 99%